Association Between Macroscopic Tongue Ischemia and Enterocyte Injury and Poor Outcome in Patients With Septic Shock: A Preliminary Observational Study. Issue 5 (November 2018) - Sekino, Motohiro; Funaoka, Hiroyuki; Sato, Shuntaro; Okada, Kyoko; Inoue, Haruka; Yano, Rintaro; Matsumoto, Sojiro; Ichinomiya, Taiga; Higashijima, Ushio; Matsumoto, Shuhei; Hara, Tetsuya
Abstract : ABSTRACT: A correlation between sublingual and intestinal mucosa microcirculation, and ischemic necrosis of the tongue as a sign of poor prognosis has been reported. However, an association between tongue ischemia and intestinal health and subsequent outcome has never been studied. This preliminary prospective observational study evaluated the association between macroscopic tongue ischemia and enterocyte injury and poor outcome in patients with septic shock. In this study, 57 adults with septic shock on mechanical ventilators were enrolled. Macroscopic tongue ischemia upon intensive care unit (ICU) admission was assessed by two independent intensivists. We used intestinal fatty-acid binding protein (I-FABP) as a biomarker of enterocyte injury and evaluated the association with tongue ischemia. Demographic variables, risk factor data, and 28-day mortality information were also collected. Compared with patients with normal tongues (n = 45), those with ischemic tongues (n = 12) had a significantly higher Acute Physiology and Chronic Health Evaluation II score (29.0 [25.0–34.0] vs. 36.5 [30.5–44.5], P = 0.017), lactate level (2.8 [2.0–5.0] vs. 9.3 [4.5–10.6], P = 0.002), and I-FABP level (1.9 [0.8–4.0] vs. 54.4 [19.5–159.3], P < 0.001) and the all-cause 28-day mortality was significantly higher (7% vs. 83%, P < 0.001). In conclusion, macroscopic tongue ischemia at ICU admission was associated with enterocyte injury and poor outcome in patients with septic shock. Although there is a disadvantage in that assessment of the tongue was subjective, tongue ischemia could be used to gauge the severity of intestinal injury and to estimate poor outcome in the clinical setting. Abstract : Supplemental Digital Content is available in the text